An Analysis of the Implementation of the Tarjamah Method in Teaching Nahwu to Grade 8 Students at PPTQ Putri Colomadu, Academic Year 2025–2026 - Atikah Syahidatul Aula; Zahrodin Fanani (Solo International Collaboration and Publication of Social Sciences and Humanities, 2026)
Objective: Analyze the implementation of the Tarjamah method in learning Mubtada' and Khabar in grade VIII students and its effectiveness in improving the understanding of nahwu. Theoretical framework: Based on the theory of nahwu learning, which integrates the understanding of meaning and grammatical structure through the translation method. Literature review: Departing from the problem that nahwu is considered difficult, a method is needed that makes it easier to understand concepts gradually. Method: Qualitative descriptive research with observations, interviews, and documentation analyzed using the Miles, Huberman, and Saldaña interactive model. Results: The results of the study show that the Tarjamah method is applied through the stages of reading Arabic texts, translating vocabulary, explaining nahwu rules, and providing exercises to identify mubtada' and khabar. The implementation of this method helps students understand the relationship between sentence meanings and grammatical structures, increases participation in learning, and facilitates the analysis of nahwu rules. However, the difference in students' initial abilities and limited learning time are still obstacles in its implementation. Implications: The Tarjamah method can be an effective alternative in learning nahwu in the pesantren environment. Novelty: This study shows the application of the Tarjamah method specifically to Mubtada' and Khabar materials as an approach that integrates translation with grammatical analysis to improve students' understanding.